A Genre-Based Approach in Teaching Arabic Writing for Higher Education Learners - Alif Cahya Setiyadi; Azmi Zarkasyi; Mochammad Firdaus; Anhar Anhar; Luthfi Muhyiddin (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2025)
This article explored the role of genre-based grammar instruction in addressing these challenges and enhancing university students' ability to write effectively in Arabic. This research employed True Experimental Research with Post-test Only Group Design. The results of the study show that GBA has considerable impact on improving student writing outcomes. The statistical analysis showed that the experimental group outperformed the control group in writing test scores, with a significant mean difference of 1.25 in favor of the experimental group. Levene’s test indicated no significant difference in variances between groups. The results further demonstrate that the use of the Genre Based Approach has a significant impact on improving students’ writing performance.